Mechanisms of vitamin D influence on the occurrence and course of acute respiratory infections, including COVID-19 - Ikrom A. Kalandarov; Ekaterina A. Slutskaya; Anastasia S. Shirokina; Khushnuda A. Bakhodurova; Margarita A. Gromova; Alexander A. Kopelev (LLC "MEDIAFORMAT", 2022)
The article discusses a possible relationship between the level of vitamin D in the blood serum and the incidence of acute respiratory infections (ARI), including viral etiology, including a new coronavirus infection that caused the recent pandemic. Views are given on the possible mechanisms of the influence of the serum level of this vitamin on the activity of various parts of the immune response. In recent years, it has been established that cells, incl. of the innate and adaptive immune systems, produce enzymes that promote the transition of the specified vitamin to the active metabolite, and this is necessary for an adequate immune response. We examined patients in whom the treatment of vitamin D deficiency contributed to a rapid recovery from ARI. Thus, maintaining optimal levels of vitamin D is important to ensure an adequate immune response, and low levels are associated with a variety of immune-related diseases, including autoimmune and infectious diseases.